Prospects of Executing the Project of Compiling a Tourism City in Afshona Village Located in Bukhara Region - Bobokalonov, Suxrob Ramazonovich (American Journal of Economics and Business Management, 2024)
This study explores the prospects of developing a tourist town in the village of Afshona, located in the Peshku district of the Bukhara region, the birthplace of the renowned scientist Abu Ali ibn Sina. Despite its historical and cultural significance, the area remains underutilized as a tourist destination, presenting a knowledge gap in leveraging such heritage for tourism development. The research aims to propose scientifically grounded, practical, and organizational-economic measures to transform Afshona into a year-round tourist hub capable of attracting over 10 million domestic and international visitors annually. Using a multidisciplinary approach, the study identifies development stages and formulates actionable recommendations. The findings highlight the potential of this project to boost regional tourism, preserve cultural heritage, and stimulate economic growth, offering valuable insights for policymakers and practitioners in tourism development.